2020
DOI: 10.14202/vetworld.2020.1517-1523
|View full text |Cite
|
Sign up to set email alerts
|

Production, immunogenicity, stability, and safety of a vaccine against Clostridium perfringens beta toxins

Abstract: Background and Aim: The beta toxin is causing the most severe Clostridium perfringens-related diseases. This work was dedicated to developing a vaccine against beta toxin using C. perfringens type C (NCTC 3180). Materials and Methods: The crude toxoid harvest contained 710 limits of flocculation (Lf)/mL. The vaccine was formulated. Each 1 mL of the final vaccine product contained at least 50 Lf/mL of beta toxoids, 0.2 mL 3% aluminum hydroxide gel (equivalent to 5.18 mg of aluminum), <0.001% W/V thiomersal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…In line with the findings of this study, evidence reports a recombinant vaccine that produces 9.6 and 5.19 IU/mL neutralizing antibodies in rabbits and cattle, respectively [17,24]. Consistent with the findings of the present study, a similar previous study conducted in 2016 indicated a 1.80-fold decrease in immune response (antibody titer) in cattle than in rabbits [21,23]. In the present study, the difference between rabbits and cattle was 3.90 IU/mL, which coincides with the value reported by a previous study on alpha-toxin [21].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with the findings of this study, evidence reports a recombinant vaccine that produces 9.6 and 5.19 IU/mL neutralizing antibodies in rabbits and cattle, respectively [17,24]. Consistent with the findings of the present study, a similar previous study conducted in 2016 indicated a 1.80-fold decrease in immune response (antibody titer) in cattle than in rabbits [21,23]. In the present study, the difference between rabbits and cattle was 3.90 IU/mL, which coincides with the value reported by a previous study on alpha-toxin [21].…”
Section: Discussionsupporting
confidence: 93%
“…Initially, C. perfringens type A, as well as its respective alpha-toxin, was inactivated by the addition of formaldehyde. This is because formaldehyde -a one-carbon, highly hydrophilic aldehydecan eliminate the damaging effects, reduce bacterial replications, and detoxify bacterial toxins [22,23]. A question then emerges regarding the exact of the formulated vaccine that can elicit and maintain immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the potency demonstrated by nanoalum in the bivalent vaccine was maintained in the multivalent vaccine. Although experimental models do not always accurately mimic the immune responses in target animals [ 37 ], the nanoalum vaccines used in this study have the potential to meet or exceed the minimum required protective immunity in target animals. Nevertheless, further experiments in field animals are required to evaluate the extent to which the nanoalum-containing vaccines induce an immunological response.…”
Section: Discussionmentioning
confidence: 99%
“…Specific K m values of species are coefficient of body surface area (for a 60-kg adult human, K m = 37, for a 20-g mouse, K m = 3) (Rattan et al 2011;Saadh et al 2020).…”
Section: Mice Immunizationmentioning
confidence: 99%